Outcome-affecting parameters of hip arthroscopy for femoroacetabular impingement with concomitant cartilage damage: data analysis from the German Cartilage Registry - Serong, Sebastian; Fickert, Stefan; Niemeyer, Philipp; Banke, Ingo J.; Goronzy, Jens; Sobau, Christian; Zinser, Wolfgang; Landgraeber, Stefan (Journal of Clinical Medicine, 2022)
This study aims to report on a prospectively collected, multicenter database of patients undergoing hip arthroscopy for femoroacetabular impingement syndrome (FAI) and concomitant cartilage damage (according to the International Cartilage Repair Society) and to assess the outcome-affecting parameters. In the study, 353 hips with up to 24 months’ follow-up were assessed by iHOT-33 scoring and achievement of the minimal clinically important difference (MCID) and patient acceptable symptom state (PASS) levels. Multiple and binary regression analyses were performed to identify factors related to (un-) favorable outcomes and to assess their clinical relevance with regard to achieving the MCID and PASS. Multiple regression yielded the parameters of male sex (p = 0.022) and lower body mass index (BMI) (p = 0.019) at 6 months, lower BMI (p = 0.022) and younger age (p = 0.022) at 12 months, and younger age at 24 months (p = 0.039) to be significantly associated with higher iHOT scoring. Male sex (p = 0.019) and lower BMI (p = 0.018) were significantly correlated with achievement of the PASS in binary regression at 6 months, whereas at 12 (p = 0.010) and at 24 (p = 0.003) only younger age was shown to be significantly correlated. None of the parameters was statistically associated with achievement of the MCID. As the parameters of younger age, male sex, and lower BMI were identified as temporarily correlated with a preferable outcome in general and with achievement of the PASS in particular, these findings help to preoperatively identify factors associated with (un-) favorable therapy results.
Gesehen am 06.05.2024